Relevansi Pemikiran Ibnu Khaldun Tentang Siklus Ekonomi dan Pajak dalam Konteks Ekonomi Modern - Pipit Pipit; Nuri Kamilatul Pikriyyah; Wafa Jannatul Mawa; Lina Marlina (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
Ibn Khaldun's thoughts in Muqaddimah on economic cycles and taxation remain relevant in the context of modern economics. He explains that the growth and decline of a nation's economy follow a cyclical pattern, where imbalanced fiscal policies can accelerate the downfall of a civilization. Ibn Khaldun emphasizes the importance of fair and proportional taxation to avoid hindering societal productivity and investment. His views on the impact of taxation on the economy align with the Laffer Curve concept, which states that excessively high taxes can actually reduce state revenue. This study employs a literature review method to analyze Ibn Khaldun’s thoughts and their relevance to modern economic systems and fiscal policies. The findings indicate that his ideas can serve as a foundation for formulating sustainable Islamic economic policies. By applying the principles of balance between taxation, production, and societal welfare, a nation can maintain long-term economic stability. Therefore, Ibn Khaldun's thoughts remain relevant as a reference for contemporary economic policies, particularly in addressing economic disparities and preventing financial crises.